2020
DOI: 10.1080/13563467.2020.1841138
|View full text |Cite
|
Sign up to set email alerts
|

Gambling and Political Economy, Revisited

Abstract: Gambling is central to our understanding of political economy, but the dominant story told about gambling within our subfield is highly partial. It focuses on globally spectacular forms and places of gambling, especially casinos. It tends to associate gambling with neo-liberal formulations of political economy. And it tends to fixate on men's play. In this article, I seek to show the value of an alternative lens on gambling and political economy, provided by the game of bingo. I hereby aim to improve our acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These findings sharpen our understanding of Canadians' gambling behaviours in a large, diverse metropolitan region. Previous research has demonstrated that individuals engage in lottery gambling for reasons beyond pure financial gain: it can become embedded in everyday life, taking on a broad range of meanings that vary across cultures and contexts (e.g., Bedford, 2021;Casey, 2008;Nicoll, 2019). The present research contributes to a growing body of work aimed at deepening our understanding of the way consumption practices inform both culture and the subjective and material realities of gamblers (Casey, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings sharpen our understanding of Canadians' gambling behaviours in a large, diverse metropolitan region. Previous research has demonstrated that individuals engage in lottery gambling for reasons beyond pure financial gain: it can become embedded in everyday life, taking on a broad range of meanings that vary across cultures and contexts (e.g., Bedford, 2021;Casey, 2008;Nicoll, 2019). The present research contributes to a growing body of work aimed at deepening our understanding of the way consumption practices inform both culture and the subjective and material realities of gamblers (Casey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aim to understand what influences people's day-to-day participation in fixed-prize gambling in a large metropolitan area in Canada. Within the sphere of gambling research, there is a growing interest in examining the relationship between gambling practices and the external environment of lottery gamblers (Bedford, 2021;Casey, 2008;Nicoll, 2019). Here we seek to expand this line of inquiry and elucidate the relationship between environmental factors and willingness to participate in gambling.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions run parallel with other significant feminist interventions that highlight the ways in which gambling provides critical pathways into other political economies such as play, leisure and consumption (Bedford 2016, 2021; Casey 2008a, 2008b). Yet, their readings of gambling also differ in one key way.…”
Section: Placing the Wagermentioning
confidence: 99%
“…His conclusions underlined that patterns of property market participation demonstrated resultant changes, but that shifts were far more notable towards the bottom of the market. Bedford addressed another area of regulation, that is, gambling, in New Political Economy , arguing the centrality of women's participation in games such as bingo to legislative reforms since the mid‐twentieth century, who have so far been overlooked in accounts centred on male‐dominated sports betting.…”
mentioning
confidence: 99%